The Noteworthiness Of Perpetual Justice In James Baldwin's The Bell Of Atri - Fennyta Diva Fadilla; Anggoro Cahyo Wicaksono; Dyah Ayu Ratna Jelita; Yovita Olivia; Rommel Utungga Pasopati; Andharu, Devito; M Reza Ishadi Fadillah (Gudang Jurnal Multidisiplin Ilmu, 2024)
This article investigates how perpetual justice is prolonged in James Baldwin’s flash fiction entitled The Bell of Atri. Drawing on theories of moral and ethical principles, this study examines the idea of justice that transcends time and its implications in the context of the narrative. There is restorative justice emphasizing on repairing the harm caused by lawlessness and restoring disturbed relationships between perpetrators, victims, and society. Through qualitative approach, this article involves the active participation in the restorative process of apology, reparation, and reconciliation. The Bell of Atri then underscores the importance of moral integrity and fairness in society as it highlights the enduring relevance of ethical principles and the significance of upholding justice across generations. In conclusion, The Bell of Atri emphasizes the importance of the perception of justice in the relationships of fellow beings and the peace within well-being conditions of others.